THE INFLUENCE OF PARENTING STYLE AND ADOLESCENT-PARENT INTERACTION ON THE SUBJECTIVE WELL-BEING OF ADOLESCENTS DURING THE COVID-19 PANDEMIC - Fariha Apriliya; Dwi Hastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The COVID-19 pandemic had a considerable impact on adolescents, including reducing adolescents activities outside the home, conducting schools online and increasing stress. This study aims to analyze the effect of parenting styles, and adolescent interactions with parents on the subjective well-being of adolescents during the COVID-19 pandemic. Research respondents were grade 12 students of SMKN 2 and SMKN 3 Bangkalan. Sampling technique using simple random sampling method with a total sample of 197 adolescents. The results of the study found that there were differences in the subjective well-being of adolescents, namely lower subjective well-being during the COVID19 pandemic. Based on the results of the study, adolescent age was significantly negatively related to the subjective well-being of adolescents before the COVID-19 pandemic. The education of father and mother is significantly positively related to adolescent-mother interaction. Adolescent age, family size, and authoritarian parenting style have a significant negative effect on the subjective well-being of adolescents before the COVID-19 pandemic. Permissive, authoritarian parenting styles, and adolescent interactions with fathers have a significant positive effect on adolescents' subjective well-being during the COVID-19 pandemic.